FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN LOW BACK PAIN PADA SOPIR IKAS (IKATAN ANGKUTAN SEKOLAH) DI KABUPATEN SEMARANG - Izzatul Alifah Sifai; Daru Lestantyo; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Low back pain (LBP) is a common complaint encountered in everyday life. Driver is a job that has a risk of health problems in the form of muscle disorders that cause LBP. The contributing factors can come from the individual itself such as age, work period, smoking habits, and body mass index. Meanwhile factors from work can come from whole body vibration (WBV) and driving posture. The purpose of this study was to analyze the correlation of age, work period, smoking habits, body mass index, WBV, and driving posture with LBP complaints. This study uses analytic observational with cross sectional research approach. The subjects of this study all IKAS driver in Semarang Regency, as much as 33 people with total sampling method. The research instrument was questionnaire, measurement trunk mobility with modified schober’s test, and photo of driving posture. The results showed that there were 30,6% of respondents experienced a decrease in spinal mobility. The results of statistical tests with the Spearman test found a correlation between LBP with age (p=0.021) and driving posture for groin angle (p=0.013) and knee angle (p=0.022). There was no correlation between working periods (p=0.116), smoking habits (p=0.186), body mass index (p=0.079), and WBV (p=0.460). Suggestions for IKAS drivers were to lose weight, stretching, and routine car maintenance.